If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying s + 6 = 78 Reorder the terms: 6 + s = 78 Solving 6 + s = 78 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + s = 78 + -6 Combine like terms: 6 + -6 = 0 0 + s = 78 + -6 s = 78 + -6 Combine like terms: 78 + -6 = 72 s = 72 Simplifying s = 72
| 2x+3y-5x+5y= | | 5(1+6a)=-39+8a | | 2+2v=-2 | | 2z^3+9z^2=5z | | 5b-16-8n=-10 | | 7(y+1)=49 | | K=17 | | X+3=-32 | | 15-f=-23 | | 4-5(x+3)=25 | | -22+7r=6(r-4) | | 3x+7+6x+11=90 | | 4x+1=11x | | -2(5y+5)=4 | | 3*x=10 | | 8+16=-3(5x-8) | | 9(6x-5)=279 | | 22x-16x+12=-15+3x+12+6x | | 5x-9=13-x | | 7=20 | | 120*24= | | -30+5n=4+4(1+6n) | | -4(x+8)=-3x-5 | | 4(y+5)=-6(2y-1)+4y | | x^2+8x+8=o | | -5x=5x-100 | | 0.8x+.06(x+9)=1.24 | | 8w-33=-5(w+4) | | 102=-5(3-5m) | | -6=18k | | 18=4(2+x)-15 | | 13-x=5x-9 |